2018
DOI: 10.1016/j.neurobiolaging.2017.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Age-related functional changes in domain-specific medial temporal lobe pathways

Abstract: There is now converging evidence from studies in animals and humans that the medial temporal lobes (MTLs) harbor anatomically distinct processing pathways for object and scene information. Recent functional magnetic resonance imaging studies in humans suggest that this domain-specific organization may be associated with a functional preference of the anterior-lateral part of the entorhinal cortex (alErC) for objects and the posterior-medial entorhinal cortex (pmErC) for scenes. As MTL subregions are differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
229
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(263 citation statements)
references
References 70 publications
25
229
7
2
Order By: Relevance
“…This phenomenon -age-related neural dedifferentiation -has been conjectured to play a role in age-related cognitive decline [20][21][22] . Notably, lower specificity of neural responses to perceptual events has been reported to predict poorer subsequent memory for the events in both young and older adults [23][24][25] . These findings raise the possibility that the distinctiveness or fidelity with which the perceptual features of an event are neurally represented at the time of encoding (that is, its level of neural differentiation) are a determinant of the fidelity with which the features are reinstated at retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon -age-related neural dedifferentiation -has been conjectured to play a role in age-related cognitive decline [20][21][22] . Notably, lower specificity of neural responses to perceptual events has been reported to predict poorer subsequent memory for the events in both young and older adults [23][24][25] . These findings raise the possibility that the distinctiveness or fidelity with which the perceptual features of an event are neurally represented at the time of encoding (that is, its level of neural differentiation) are a determinant of the fidelity with which the features are reinstated at retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…Although subsequent studies have reported convergent findings, the data suggest that age-related dedifferentiation is not ubiquitous. For example, whereas reduced neural selectivity is frequently reported in scene-selective (Carp et al 2011;Voss et al, 2008;Zheng et al, 2018; and face-selective cortical regions Voss et al, 2008;Park et al, 2012), null findings for both of these classes of stimuli have also been reported (for scenes: Berron et al, 2018; for faces : Payer, et al, 2016). The evidence is also divergent for object and word stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have used a repetition sensitivity approach (see Kim, 2017 for a review), in which regions sensitive to repetition are first identified by comparing activity to repeated and novel stimuli. Within these repetition-sensitive regions, the neural signature of successful MD is observed as activity to lures that is different from repeated targets and similar to novel stimuli, which has been observed in hippocampus (Berron et al, 2018) and its subfields, specifically the dentate gyrus/cornu ammonis 3 (DG/CA3; Azab, Stark, & Stark, 2014;Bakker, Kirwan, Miller, & Stark, 2008;Kirwan & Stark, 2007;Lacy et al, 2011). In some cases, a lure-similarity approach has been used in conjunction with the repetition sensitivity approach by first identifying regions sensitive to repetition and then testing whether activity to lures that parametrically vary in their degree of similarity to targets is significantly different from repeated targets but not novel stimuli (Lacy et al, 2011).…”
mentioning
confidence: 99%